Computer aided learning knowledge among medical students in the Faculty of Medicine and Health Sciences, Universiti Putra Malaysia - Mohd Sidik, Sherina; Abdullah, Mohd Yunus; S. A., Azlan Hamzah; Md. Zain, Azhar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2009)
Computer proficiency has become necessary in many areas of medicine, administration, clinical practices, research, as well as education. The need for greater competence in information and communication technologies (ICT) by doctors and medical students is increasingly recognised. Objectives: This study was undertaken to determine the knowledge, attitude and practices on ICT in the medical students of a local university. Methods: A cross-sectional descriptive study was conducted among medical students (Years 1-5) from December 2005 to May 2006 in Universiti Putra Malaysia. A self-administered questionnaire was used to collect data. Descriptive statistics were used to obtain frequencies for all variables studied. Results: There were 343 respondents aged 18-29 years old. The results showed 82.2% of the respondents (82.2%) were comfortable using computers after entering medical school and 89.2% believed that ICT and computers skills are important for doctors. About 81.3% of the respondents were aware of the role of ICT and computers in learning medicine, 90.4% had used presentation packages, and 83.4% used word processing and search engines as software tools. Conclusion: The findings of this study show that medical students are knowledgeable and do have skills in information technology (IT) and computers. They are also aware of the role of information technology (IT) and computers in medicine